Evaluation of Totarol for Promoting Open Wound Healing in Dogs - Somphong Hoisang; Supranee Jitpean; Suvaluk Seesupa; Phanthit Kamlangchai; Tossawarn Makpunpol; Pimsiri Ngowwatana; Saikam Chaimongkol; Duangdaow Khunbutsri; Jeerasak Khlongkhlaeo; Naruepon Kampa (Veterinary Sciences, 2024)
This study investigates the susceptibility of common pathogens to totarol and assesses its clinical effectiveness in promoting wound healing in client-owned dogs with open wounds. Twenty-three client-owned dogs with open wounds were divided into two groups: (1) the treatment group (T-group) and (2) the control group (C-group). Clinical samples were collected from the wounds for the bacterial identification and determination of the minimum inhibitory concentrations (MICs) of totarol. In the T-group, wounds were treated with standard wound care together with the application at a dosage of 0.3 mL (two sprays) of commercial totarol product per 25 cm2 of the wound area. The C-group received only standard wound care. This in vitro study found that totarol exhibited antimicrobial activity against both standard pathogens and clinical wound pathogens. The MIC values of totarol dissolved in absolute ethyl alcohol were 4 µg/mL for Gram-positive pathogens and ranged from 256 to 512 µg/mL for Gram-negative pathogens. However, the MIC values of the commercial totarol product ranged from 512 to 1024 for both Gram-positive and Gram-negative pathogens. Clinically, the use of a commercial totarol product as an adjunctive therapy significantly improved wound healing, as indicated by a greater percentage of wound area reduction (p < 0.05). From day 2 to day 7 of the treatment, the percentage of wound area reduction differed significantly between the T-group and the C-group. At the end of the study, the average percentage of wound area reduction was 69.18% ± 18.12 and 41.50% ± 20.23 in the T-group and C-group, respectively. The finding of this study illustrates the antimicrobial properties of totarol and its product against prevalent wound pathogens. These results suggest the potential of totarol as an adjunctive option for canine wound care.